Look Like Me: Matching Robot Personality via Gaze to Increase Motivation - Andrist, Sean; Mutlu, Bilge; Tapus, Adriana (33rd Annual ACM Conference on Human Factors in Computing Systems (CHI ’15), 2015)
Socially assistive robots are envisioned to provide social and cognitive assistance where they will seek to motivate and engage people in therapeutic activities. Due to their physicality, robots serve as a powerful technology for motivating people. Prior work has shown that effective motivation requires adaption to user needs and characteristics, but how robots might successfully achieve such adaptation is still unknown. In this paper, we present work on matching a robot's personality-expressed via its gaze behavior-to that of its users. We confirmed in an online study with 22 participants that the robot's gaze behavior can successfully express either an extroverted or introverted personality. In a laboratory study with 40 participants, we demonstrate the positive effect of personality matching on a user's motivation to engage in a repetitive task. These results have important implications for the design of adaptive robot behaviors in assistive human-robot interaction.
Best of CHI Honorable Mention Award